Parabolic Transcendence in Time and Narrative Journal for Religion, Film and Media - Joel Mayward (Journal for Religion, Film and Media, 2020)
Subjectivity, memory, identity, and the invisible connections between individuals are all conspicuous within filmmaker Shane Carruth's two award-winning indie sci-fi films, Primer (Shane Carruth, USA, 2004) and Upstream Color (Shane Carruth, USA, 2013). In this, I contend that both Primer and Upstream Color are post-secular cinematic parables per philosopher Paul Ricoeur's description of parable: the conjunction of a narrative form and a metaphorical process, addressing the religious via non-religious discourse. Interpreting these two films through a Ricoeurian parabolic hermeneutic addresses their mutual transcendence in and through time and narrative via their striking visual and auditory aesthetics, the use of montage in their nonlinear narratives, and the depiction of invisible relational connections between the films' protagonists. I conclude that Carruth's post-secular cinema resides in an in-between space: between the secular and the religious, realism and expressionism, immanence and transcendence.